Detection of eae Gene as A Marker Strain EPEC (Enteropathogenic Escherichia coli) in Chicken Meat Sold at Some Traditional Markets in Surabaya - Amrullah, Amirul Muslim; Rantam, Fedik Abdul; Raharjo, Dadik; Tyasningsih, Wiwiek; Estoepangestie, Agnes Theresia Soelih; Tacharina, Martia Rani (Journal of Basic Medical Veterinary, 2022)
This study aimed to detect the presence of eae gene in E. coli from chicken meat sold at the traditional market Surabaya. Identification of bacteria was carried out in several stages, inoculated on pre-enrichment media using Buffered Peptone Water (BPW), planting on Levine's Eosin Methylene Blue Agar (L-EMB) media, suspected colonies on L-EMB were subjected to Triple Sugar Iron Agar (TSIA) and Indol test for the confirmation of E. coli. The confirmed E. coli isolates were tested by Polymerase chain reaction (PCR) to determine the presence of the eae gene. The results showed that E. coli could be identified in 28 out of 100 (28%) chicken meat samples, and eae gene was detected in three E. coli isolates (11%).